PERANCANGAN APLIKASI MATEMATIKA MATERI KAIDAH PENCACAHAN DAN PELUANG KEJADIAN MAJEMUK BERBASIS ANDROID - Retno Tri Vulandari; Bentar Putra Pamungkas (Universitas Swadaya Gunung Jati., 2021)
Along with the development of technology, some students have left learning with books because it is easier to find knowledge on the internet. But everything listed on the internet is abstract, and not all can be accessed by Android. Therefore an android application is needed to make it easier for students. The design of this android contains learning Mathematics, rules of enumeration and opportunities for multiple events for high school. This application uses data collection methods in the form of material from books, the internet, and various other sources. Development methods include system analysis, system design and system testing. The design of this application uses Adobe Flash to make applications and Android as compailer. The programming language used is action script 3.0.Â